2013
DOI: 10.3389/fncom.2013.00023
|View full text |Cite
|
Sign up to set email alerts
|

Neural bases of hand synergies

Abstract: The human hand has so many degrees of freedom that it may seem impossible to control. A potential solution to this problem is “synergy control” which combines dimensionality reduction with great flexibility. With applicability to a wide range of tasks, this has become a very popular concept. In this review, we describe the evolution of the modern concept using studies of kinematic and force synergies in human hand control, neurophysiology of cortical and spinal neurons, and electromyographic (EMG) activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
201
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(209 citation statements)
references
References 175 publications
(209 reference statements)
6
201
0
2
Order By: Relevance
“…Analyses of intra-individual consistency and inter-player agreement in the (nonverbal) preference and attribute judgments showed that while violinists generally agreed on what particular attributes they look for in an instrument, the perceptual evaluation of the same attributes varied dramatically across individuals, thus resulting in large interplayer differences in the preference for violins. A third experiment [58] and studies by Fritz et al [26,27] and Wollman et al [66,67] reached similar conclusions.…”
Section: Touch and The Conceptualization Of Violin Quality By Musicianssupporting
confidence: 69%
See 1 more Smart Citation
“…Analyses of intra-individual consistency and inter-player agreement in the (nonverbal) preference and attribute judgments showed that while violinists generally agreed on what particular attributes they look for in an instrument, the perceptual evaluation of the same attributes varied dramatically across individuals, thus resulting in large interplayer differences in the preference for violins. A third experiment [58] and studies by Fritz et al [26,27] and Wollman et al [66,67] reached similar conclusions.…”
Section: Touch and The Conceptualization Of Violin Quality By Musicianssupporting
confidence: 69%
“…The entire sensorimotor system, much of which is dedicated to the hand, is implemented following a hierarchical organisation with nuclei in the dorsal column, the brain stem, the midbrain, the cerebellum and ultimately several cortical regions. The considerable literature on the subject can be approached through recent books and surveys [10,51,67].…”
Section: Hand Mobilitymentioning
confidence: 99%
“…This finding suggests that PreM-INs contribute to the synergistic control of primate hand movements (9,(13)(14)(15), but this question has not been examined directly. We hypothesize that if PreM-INs underlie the generation of muscle synergies, then (i) the distribution of muscle fields will exhibit significant clustering corresponding to extant muscle synergies, rather than being uniform, and (ii) the activities of PreM-INs will be temporally associated with the muscle synergies.…”
mentioning
confidence: 97%
“…At the muscle level, different works explored patterns of muscle activity whose timing and/or amplitude modulation enables the generation of different movements, see d ' Avella and Lacquaniti (2013) for a review. Synergies have also been identified and defined as covariation patterns of joint angles, e.g., hand postural synergies (Santello et al, 1998(Santello et al, , 2013Mason et al, 2001), or covariation patterns among digit forces [for a review see Zatsiorsky and Latash (2004)]. However, to correctly understand human manipulation, in addition to hand analysis, the role of whole upper limb movements should be also taken into account.…”
Section: Introductionmentioning
confidence: 99%